1962
DOI: 10.1530/jrf.0.0040047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drugs Affecting the Autonomic System on Seminal Ejaculation

Abstract: Summary. Rabbits and boars were used to study the effect on the ejaculation process of various drugs known to affect the autonomic nervous system. Of those tried, only atropine had an effect, causing linear reduction, as the dose increased, of the logarithm of the number of spermatozoa ejaculated by rabbits. In the boar, the volume ofsemen was reduced, but at the dose levels employed total spermatozoa per ejaculate changed little. This suggests that the male accessory sex glands are partly controlled by the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1963
1963
1991
1991

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Effect of atropine on boar semen 103 ANALYTICAL METHODS Immediately after each collection the total volume of semen and proportion of 'fluid' and 'gel' was recorded. In each sample of the fluid portion, the con¬ centration of spermatozoa was estimated, as previously described by Dziuk & Norton (1962). Fructose and ergothioneine were determined in ethanolic extracts from the semen (Mann, 1946;Mann & Leone, 1953;Glover & Mann, 1954) as follows: 3 ml of semen (fluid portion) were precipitated with 18 ml ethanol, the mixture centrifuged, the precipitate washed with 10 ml 75% (v/v) ethanol, the combined ethanolic extracts distilled to remove ethanol, the aqueous residue treated with 0-5 ml 0-3 N-Ba(OH)2 and 0-5 ml 5% ZnSOW^O and after adjusting the volume to exactly 6 ml, centrifuged.…”
Section: Collection Of Semenmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of atropine on boar semen 103 ANALYTICAL METHODS Immediately after each collection the total volume of semen and proportion of 'fluid' and 'gel' was recorded. In each sample of the fluid portion, the con¬ centration of spermatozoa was estimated, as previously described by Dziuk & Norton (1962). Fructose and ergothioneine were determined in ethanolic extracts from the semen (Mann, 1946;Mann & Leone, 1953;Glover & Mann, 1954) as follows: 3 ml of semen (fluid portion) were precipitated with 18 ml ethanol, the mixture centrifuged, the precipitate washed with 10 ml 75% (v/v) ethanol, the combined ethanolic extracts distilled to remove ethanol, the aqueous residue treated with 0-5 ml 0-3 N-Ba(OH)2 and 0-5 ml 5% ZnSOW^O and after adjusting the volume to exactly 6 ml, centrifuged.…”
Section: Collection Of Semenmentioning
confidence: 99%
“…It was recently shown by Dziuk & Norton (1962) that if atropine sulphate is injected into a boar, and an ejaculate collected about 30 min later, the semen thus obtained has a much reduced volume, and very little 'gel', but at the same time it has a much higher concentration of spermatozoa, so that the total absolute number of spermatozoa appears to be practically unaltered. The object of the present study was to determine, with the help of quantitative chemical methods of semen analysis, which accessory organs are affected by atropine, and to decide whether atropine acts by preventing the voidance of preformed secretions stored in the accessory glands, or by inhibiting the secretory activity of these organs, at the time of ejaculation.…”
Section: Introductionmentioning
confidence: 99%
“…Pilocarpine (50 mg) administered to the boar 20 min before semen collection had no detectable effect on either ejaculation or semen composition. However, the volume of fluid semen, the total volume of semen, and the time required for ejaculation differed significantly (P<0\m=.\01) between breeds of boars.Atropine, a parasympathetic-blocking drug, has been found to reduce the volume of semen with little or no effect on the total number of spermatozoa ejaculated by the boar (Dziuk & Norton, 1962). Differences in composition of the semen from atropine-treated and control boars indicated that atropine suppressed the secretion of the urethral glands (Dziuk & Mann, 1963).…”
mentioning
confidence: 99%
“…Atropine, a parasympathetic-blocking drug, has been found to reduce the volume of semen with little or no effect on the total number of spermatozoa ejaculated by the boar (Dziuk & Norton, 1962). Differences in composition of the semen from atropine-treated and control boars indicated that atropine suppressed the secretion of the urethral glands (Dziuk & Mann, 1963).…”
mentioning
confidence: 99%
“…Epinephrine has been found to reduce both the semen volume and spermatozoan concentration of the bull ejaculate (VanDemark & Baker, 1953). Carbachol, a powerful parasympathomimetic agent, and dibenamine, which effectively prevents the excitatory responses of smooth muscle and exocrine gland cells to adrenergic stimuli, have no effect on copulatory behaviour in rabbits (Dziuk & Norton, 1962). Atropine reduces the total volume of semen and increases the spermatozoan concentration of the boar (Dziuk & Norton, 1962;Dziuk & Mann, 1963) and bull ejaculates (Signoret, 1962 (1934).…”
Section: Introductionmentioning
confidence: 99%